OS JESUÍTAS E SUA INFLUÊNCIA NO ENSINO DA ARTE EM JERUMENHA/ PI - César Messias da Conceição, Domingas; Maria de Sousa, Tânia; Lima de Oliveira, Uilisneide; Pessôa Araújo Meireles, Melise (Revista Form@re - Parfor/UFPI, 2026)
.